A Critique on the Theory of the Necessity of the Oneness of Consort (Faá¸¥l) - Ã˜ÂÃ˜Â§Ã˜Â¦Ã˜Â±Ã›ÂŒ, Ã™ÂÃ˜Â§Ã˜Â·Ã™Â…Ã™Â‡; Ã™Â†Ã˜Â§Ã˜ÂµÃ˜Â±Ã›ÂŒ Ã™Â…Ã™Â‚Ã˜Â¯Ã™Â…, Ã˜ÂÃ˜Â³Ã›ÂŒÃ™Â†; Ã™Â‚Ã˜Â¨Ã™ÂˆÃ™Â„Ã›ÂŒ Ã˜Â¯Ã˜Â± Ã˜Â§Ã™ÂÃ˜Â´Ã˜Â§Ã™Â†, Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯ Ã˜ÂªÃ™Â‚Ã›ÂŒ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Among the causes for the prohibition of marriage is fosterage, which is one of the most important issues of concern. There is consensus among the jurists of all the Islamic schools in that fosterage is one of the causes of prohibition. However, the issue disagreed upon is whether the source in fosterage causing the spread of sanctity (á¸¥urma) is the mother (murá¸iâa = foster mother) or the father (á¹£Äá¸¥ib laban = possessor of milk). The renowned majority of ImÄmÄ«s believe that what is valid in the spread of sanctity in fosterage is the oneness of the consort (faá¸¥l); and their reason is (based on) the traditions that cause specification and limitation of several generalities, such as the Prophetâs (S.A.W) á¸¥adÄ«th, âWhat is prohibited through fosterage would be prohibited through parentage (nasab), tooâ, and the verse of the QurâÄn, ï´¾your [foster-] mothers who have suckled you and your sisters through fosterageï´¿. (Al-NisÄâ, 23) The renowned disapproving majorityâs statement is that of á¹¬abarsÄ«, the author of TafsÄ«r al-BayÄn, and another group of the ImÄmÄ«s, who have not considered as a precondition the oneness of consort in the fosterage causing the spread of prohibition. The reason for this statement is the generality of á¸¥adÄ«th, inclusiveness of the verse, and the traditions of Muá¸¥ammad b. âUbayda. The critical review of the two viewpoints and their reasons reinforce the unrenowned majorityâs statement.